PENENTUAN PEMENANG TENDER YANG BERPOTENSI MELANGGAR LARANGAN PERSEKONGKOLAN TENDER: Determination Of Tender Winners Who Have The Potential To Violate The Prohibition Of Tender Conspiracy - Rahmadhani, Zahra Fide; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2025)
The global economy requires Indonesia to grow as a force in the new economy. This is expected to support national development and create a competitive market situation among them. This condition causes competition, can run in a healthy and unhealthy way. One of the activities that can cause unfair business competition is the process of procurement of goods and/or services, known as tenders. In fact, many business actors run tenders with bad intentions, which is called tender conspiracy. Using normative legal methods by collecting library materials from primary, secondary and tertiary materials to produce descriptive data, then ending with a conclusion using the concept of agreement based on the Civil Code that conspiracy is a prohibited agreement. . In determining the winner of the tender, what is considered to be a violation of Article 22 is vertical conspiracy because it results in unhealthy business competition. This shows that there must be updates in the provisions regarding business competition, especially provisions regarding bid rigging, and tender selection must be carried out through appropriate and accurate procedures. For example, the selection of the tender committee must be qualified, have integrity and be honest in carrying out the tender. Settlement in cases of conspiracy to determine tender winners can be implemented using a per se illegal approach carried out by the KPPU to assess business activities that violate the provisions of Law Number 5/1999